2003
DOI: 10.1016/s0029-7844(03)00669-0
|View full text |Cite
|
Sign up to set email alerts
|

Trends in gestational choriocarcinoma: a 27-year perspective*1

Abstract: Gestational choriocarcinoma incidence rates have declined and survivals have improved, but blacks continue to have higher incidence and lower survival rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 34 publications
2
32
0
2
Order By: Relevance
“…It is less likely that inadequacy of postmolar surveillance guidelines contributed significantly because clear guidelines exist for diagnosis of and surveillance after GTD. 15 Our results affirm many of the findings of an earlier SEER analysis by Smith et al, 9 who evaluated patients with choriocarcinoma from 1973 to 1999. Like these authors, we also showed that most patients with choriocarcinoma are diagnosed from ages 20 to 39 years and that there is no difference in the distribution of choriocarcinoma by stage and race.…”
Section: 048supporting
confidence: 85%
See 3 more Smart Citations
“…It is less likely that inadequacy of postmolar surveillance guidelines contributed significantly because clear guidelines exist for diagnosis of and surveillance after GTD. 15 Our results affirm many of the findings of an earlier SEER analysis by Smith et al, 9 who evaluated patients with choriocarcinoma from 1973 to 1999. Like these authors, we also showed that most patients with choriocarcinoma are diagnosed from ages 20 to 39 years and that there is no difference in the distribution of choriocarcinoma by stage and race.…”
Section: 048supporting
confidence: 85%
“…The analysis of age-adjusted cancer incidence, however, was limited to patients diagnosed from 2000 to 2014 because data from 1973 to 1999 have been previously evaluated. 9 Patients with choriocarcinoma were identified on the basis of their International Classification of Diseases for Oncology, Third Edition (ICD-O-3) code. 10 Patients with the histologic code for choriocarcinoma (9100/3) were included.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Deregulation in this pseudomalignant phenotype results in the development of GTDs [42] and PE [43] which involves excessive or shallow invasion of trophoblasts into myometrium, respectively. Recent studies have suggested existence of common epigenetic mechanisms between trophoblasts and cancer cells, regulating proliferative, migratory and invasive properties [40,44].…”
Section: Discussionmentioning
confidence: 99%